Het door Eduard Cuypers ontworpen gebouw. Het Veiligheidsmuseum was hier gevestigd van 1914 tot 1983
Het door Eduard Cuypers ontworpen gebouw. Het Veiligheidsmuseum was hier gevestigd van 1914 tot 1983.